2023
DOI: 10.3389/fmicb.2023.1128497
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance in Helicobacter pylori infection

Abstract: Helicobacter pylori (Hp), a well-known human pathogen, causes one of the most common chronic bacterial infections and plays an important role in the emergence of chronic progressive gastric inflammation and a variety of gastrointestinal diseases. The prevalence of Hp infection varies worldwide and is indirectly proportional to socio-economic status, especially during childhood. The response to the eradication therapy significantly depends on the antibiotic resistance specific to each geographical region; thus,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 102 publications
0
13
0
Order By: Relevance
“…Hp biofilms treated in vitro with clarithromycin displayed an increased minimum bactericidal concentration and minimum inhibitory concentration, as well as a higher mutation rate, which contributes to their already significant genotypic variation [ 61 , 62 ]. There is also emerging resistance of Hp to other antibiotics such as levofloxacin and metronidazole [ 63 ]. In addition to becoming multi-drug-resistant, Hp biofilms successfully defend against the host immune response.…”
Section: Biofilm-associated Helicobacter Pylori An...mentioning
confidence: 99%
“…Hp biofilms treated in vitro with clarithromycin displayed an increased minimum bactericidal concentration and minimum inhibitory concentration, as well as a higher mutation rate, which contributes to their already significant genotypic variation [ 61 , 62 ]. There is also emerging resistance of Hp to other antibiotics such as levofloxacin and metronidazole [ 63 ]. In addition to becoming multi-drug-resistant, Hp biofilms successfully defend against the host immune response.…”
Section: Biofilm-associated Helicobacter Pylori An...mentioning
confidence: 99%
“…Some earlier reports between 2000 and 2005 quantify changes in antimicrobial resistance within H. pylori infection to metronidazole, clarithromycin, amoxicillin and tetracycline [40]. Other reviews consider antimicrobial resistance further in 2023 during H. pylori infection [41].…”
Section: Helicobacter Pylori Epidemiology and Other Factorsmentioning
confidence: 99%
“…The escalating antibiotic resistance of HP has compromised the effectiveness of commonly used antimicrobial agents such as clarithromycin, levofloxacin, and metronidazole, often leading to failure in eradicating the infection [ 20 , 21 , 22 , 23 , 24 ]. Research has indicated that the global resistance of HP to antibiotics has reached alarming levels, significantly undermining the efficacy of treatment [ 25 ].…”
Section: Introductionmentioning
confidence: 99%